2002
DOI: 10.1524/ract.2002.90.9-11_2002.683
|View full text |Cite
|
Sign up to set email alerts
|

The effect of α-isosaccharinic acid on the stability of and Th(IV) uptake by hardened cement paste

Abstract: Hardened cement paste / Stability / Thorium / Sorption / Isosaccharinic acid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Studies with Th(IV) [13][14][15][16][17][18] report strong uptake behaviour with sorption distribution ratios ( d values) typically ≥ 10 5 L kg −1 . Th(IV) uptake by cementitious materials was interpreted in terms of innersphere complexation at the surface of the C-S-H phases in cement [16,18]. Recently, an EXAFS study showed that C-S-H phases are responsible for Np(IV) retention by hardened cement paste (HCP) and that Np(IV) is predominantly incorporated in the interlayer of C-S-H phases [19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies with Th(IV) [13][14][15][16][17][18] report strong uptake behaviour with sorption distribution ratios ( d values) typically ≥ 10 5 L kg −1 . Th(IV) uptake by cementitious materials was interpreted in terms of innersphere complexation at the surface of the C-S-H phases in cement [16,18]. Recently, an EXAFS study showed that C-S-H phases are responsible for Np(IV) retention by hardened cement paste (HCP) and that Np(IV) is predominantly incorporated in the interlayer of C-S-H phases [19].…”
Section: Introductionmentioning
confidence: 99%
“…They also could be sorbed onto the HCP surface with a competing effect on anionic RN uptake. The influence of organics such as isosaccharinic acid (ISA), the most important degradation product of cellulose, on the behaviour of cationic fission products and actinides has already been studied in cementitious solution and materials [6][7][8][9][10][11]. The sorption of ISA on undegraded HCP surface has already been observed and measured [12], and its competing effect on anionic species sorption onto HCP has already been observed [13].…”
Section: Introductionmentioning
confidence: 99%
“…Isosaccharinic acid (ISA) was found to be the main degradation product [29]. ISA forms stable complexes, especially with tri-and tetravalent nuclides and can significantly influence the sorption of radionuclides [30][31][32]. The extent of the effect, however, depends on the ISA concentration in solution.…”
Section: Influence Of Organics and Colloidsmentioning
confidence: 99%
“…The aqueous ISA concentration was estimated to be below ~ 3.10 -7 M based on realistic assumptions concerning the cellulose inventory, the degree of degradation and the extent of sorption under repository conditions [4]. Note that no effect of ISA on the uptake of the safety-relevant radionuclides by HCP has been observed experimentally at this concentration level [30,32,34].…”
Section: Influence Of Organics and Colloidsmentioning
confidence: 99%